Menopause, the beginning of aging for Chilean women: A qualitative study - Araya, Alejandra Ximena; Urrutia, Maria Teresa; Dois, Angelina; Carrasco, Paola (Investigación y Educación en Enfermería, 2017)
Objective. To develop the meaning of menopause of a group of post-menopausal women and their relationship with aging. Methods. Qualitative descriptive study on 15 Chilean women that completed a taped face-to-face in depth interview that were interpreted according to Krippendorff. Results. A qualitative content analysis revealed the presence of two themes: (a) Cessation of women´s reproductive stage and (b) a life transition to aging. Conclusion. Women perceived their menopause as the beginning of aging focusing on the end of fertility and the social connotation that this new role implies. Feeling old 10 years before the customary beginning of old age is an important starting point to be incorporated in women’s health education. How to cite this article: Araya AX, Urrutia MT, Dois A. Menopause, the beginning of aging for Chilean women: A qualitative study. Invest. Educ. Enferm. 2017; 34(1):